The optimization of air-breathing micro direct methanol fuel cell using response surface method. (1st February 2015) - Yuan, Zhenyu; Yang, Jie; Zhang, Yufeng; Zhang, Xiwei
Abstract: In this paper, the response surface methodology is applied to optimize the operating conditions of μDMFC (micro direct methanol fuel cell). Three operating parameters, the methanol flow rate, the methanol concentration and the cell temperature are considered in this study, and the ranges of them are 0.5–1.5 ml min −1, 0.5–2.0 mol L −1 and 20–60 °C respectively. The individual effects of these operating parameters and the combined effects of multiple operating conditions on air-breathing cell performance are examined. Furthermore, a quadratic model is established to describe the maximum power density and open-circuit voltage as the response value. Highlights: A μDMFC (micro direct methanol fuel cell) with 0.64 cm 2 is fabricated to validate the response surface method. The method can predict the experimental results accurately. Experimental parameter optimization is conducted. The combined effect of different operating conditions is examined.